Localization dynamics of N-acetylglucosamine transporter, Ngt1 in Candida albicans. Issue 5 (27th May 2022) - Roy, Kasturi; Ghosh, Swagata
Abstract : The amino sugar N-acetylglucosamine (GlcNAc), widely present in multiple cell-surfaces is efficiently utilized by human pathogen Candida albicans at the sites of infection as a survival strategy in different host niches. GlcNAc import inside the cell is mediated by GlcNAc transporter, Ngt1. In this present study, to investigate the Ngt1 dynamics, we have checked the sensitivity of Ngt1 for GlcNAc, expression kinetics and dynamics of Ngt1, stability of Ngt1 in the presence of unrelated carbon source like, glucose and endocytic trafficking of Ngt1. For this study we have used epi-fluorescence microscopy, Western blot and Northern blot analysis. We have observed that Ngt1 expression is prolific and highly sensitive to even minute amount (<2 μM) of GlcNAc. Ngt1 maintains its turnover in the plasma membrane by sugar stimulated endocytosis via UBI4 (polyubiquitin encoding locus) mediated ubiquitylation. Co-localization studies with different sub-cellular markers have revealed that Ngt1 follows a trafficking route via early endosome-late endosome-multi vesicular body (MVB)-Trans Golgi network for degradation. In conclusion, the study will provide a better understanding of endosomal trafficking for other membrane proteins in particular sugar transporters and also will open new therapeutic aspects in Candida albicans.